Quō Vādis theoretical physics and cosmology? from Newton’s Metaphysics to Einstein’s Theology - Malek, Abdul (Annals of Mathematics and Physics, 2023)
The crisis in modern theoretical physics and cosmology has its root in its use, along with theology as a ruling-class tool, since medieval Europe. The Copernican revolution overthrowing the geocentric cosmology of theology led to unprecedented social and scientific developments in history. But Isaac Newton’s mathematical idealism-based and on-sided theory of universal gravitational attraction, in essence, restored the idealist geocentric cosmology; undermining the Copernican revolution. Albert Einstein’s theories of relativity proposed since the turn of the 20th century reinforced Newtonian mathematical idealism in modern theoretical physics and cosmology, exacerbating the crisis and hampering further progress. Moreover, the recognition of the quantum world - a fundamentally unintuitive new realm of objective reality, which is in conflict with the prevailing causality-based epistemology, requires a rethink of the philosophical foundation of theoretical physics and cosmology in particular and of natural science in general.